STUDY ON WIRE ELECTRICAL DISCHARGE MACHINING (WEDM) PROCESS UNDER THE CONDITIONS OF ULTRASONIC ACTIVATION OF THE DIELECTRIC FLUID (Nonconventional Technologies Review, 2022)
In this paper, few mechanisms for removing material by Wire Electrical Discharge Machining (WEDM), with ultrasonic activated wire electrode are analyzed. Vibrations with an ultrasonic frequency of the wire electrode to the dielectric fluid from gap have been transmitted, influencing the performances of the WEDM process. The study is focuses on the phenomena that occur in dielectric fluid, as: the priming of the electrical discharge, the electrical discharge evolution, and the physic-chemical effects into the gap, as well the material removal. We found that the ultrasonic energy transferred to the dielectric fluid from the gap intensifies the electro-erosive phenomena, beginning with the emergence of the gaseous phase and the initiation of the discharge channel, and ending with the evacuation of erosion particles.
Keywords: wire electrode ultrasonic activated; WEDM process in ultrasonic field; material remove from the workpiece; ultrasonic cavitation bubbles